2021
DOI: 10.1093/dnares/dsab001
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-scale genome assembly of Japanese pear (Pyrus pyrifolia) variety ‘Nijisseiki’

Abstract: Aim We analyzed the genome sequence of a Japanese pear (Pyrus pyrifolia) to facilitate its genetics and genomics as well as breeding programs, in which a variety ′Nijisseiki′ with superior flesh texture has been used as a parent for most Japanese pear cultivars. Methods and results De novo assembly of long sequence reads covered 136× of the Japanese pear genome and generated 503.9 Mb contigs consisting of 114 sequences with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The clean reads were further trimmed using Trimmomatic and trimmed reads shorter than 50 bp were discarded. The trimmed reads mapped to the pear genomes, including P. bretschneideri , ( 30 , 85 ), P. betuleafolia ( 86 ), and P. pyrifolia ( 87 ) were identified and removed by Bowtie2 software ( 88 ), resulting in a total of 100 GB clean reads. Kraken2 and Bracken were used for annotation and abundance assessment of microbial species, resulting in archaea (93,666), bacteria (17,032,193), phage (459), and plants and fungi (77,964) categories.…”
Section: Methodsmentioning
confidence: 99%
“…The clean reads were further trimmed using Trimmomatic and trimmed reads shorter than 50 bp were discarded. The trimmed reads mapped to the pear genomes, including P. bretschneideri , ( 30 , 85 ), P. betuleafolia ( 86 ), and P. pyrifolia ( 87 ) were identified and removed by Bowtie2 software ( 88 ), resulting in a total of 100 GB clean reads. Kraken2 and Bracken were used for annotation and abundance assessment of microbial species, resulting in archaea (93,666), bacteria (17,032,193), phage (459), and plants and fungi (77,964) categories.…”
Section: Methodsmentioning
confidence: 99%
“…Although two ACSs have been found in sand pear [4], there are likely to be unidentified ACS genes in the pear genome, and their relationship with ripening behavior is unknown. Currently, the full-length genome of sand pear (P. pyrifolia) has been sequenced, providing valuable gene resources for further functional genomics study [30]. In this study, a total of 13 ACS genes were found in the genome of sand pear, and the number is the same as that identified in P. ussuriensis [34].…”
Section: Discussionmentioning
confidence: 72%
“…2' in three ripening stages, including 1 (pre-ripening, 30 days before harvest), 2 (at harvest) and 3 (fruit senescence, 10 days after harvest). Over 89.2% of clean reads were uniquely mapped to the sand pear genome [30]. Expression of 13 PpyACSs in the pear genome was detected.…”
Section: Rna-seq Of Sand Pear Fruit and Identification Of Ppyacssmentioning
confidence: 99%
“…The sequenced and annotated genome data of Potentilla anserina (Pan) [ 16 ], Potentilla micrantha (Pmi) [ 31 ], Fragaria vesca (Fve) [ 32 ], Rosa rugosa (Rru) [ 22 ], and Pyrus pyrifolia (Ppy) [ 33 ] of Rosaceae were requested from the Genome Database for Rosaceae (GDR) ( , accessed on 14 March 2023), while the sequence of Vitis vinifera (Vvi) [ 20 ] was downloaded from the National Center for Biotechnology Information (NCBI) database. Oryza sativa (Osa) and Arabidopsis thaliana (Ath), serving as outgroups, were also downloaded from the NCBI.…”
Section: Methodsmentioning
confidence: 99%